CORPORATE DIVERSITY AND FINANCIAL PERFORMANCE OF QUOTED OIL AND GAS FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
This study examined the nexus between corporate diversity and financial performance of quoted oil and gas firms in Nigeria for a twelve (12) year period spanning from 2010-2021. The specific objectives of this study were to examine the relationship between national diversity, ethnic diversity, age diversity and market value added. Panel data were used in this study, which were obtained from the annual reports and accounts of the eleven (11) sampled listed oil and gas firms. Ex-Post Facto research design was employed. Descriptive statistics of the dataset from the sampled firms was employed to summarily describe the mean, standard deviation, minimum and maximum values of the data for the study variables. Inferential statistics using Pearson correlation coefficient and Panel least square regression analysis were employed to test the hypotheses of the study. The results reported that there is a significant and positive relationship between national diversity and market value added (β1 = 1.849415; p-value = 0.0000 < 0.05); a significant and positive relationship between ethnic diversity and market value added (β2 = 2.004632; p-value = 0.0000 < 0.05) and a significant and positive relationship between age diversity and market value added (β3 = 5.226703; p-value = 0.0000 < 0.05) of listed oil and gas firms in Nigeria at 5% level of significance. Conclusively, the study found a positive relationship between corporate diversity and financial performance of listed oil and gas firms in Nigeria at 5% level of significance.  The study recommended inter alia that firms should imbibe the ideology of corporate diversity, which will help dispel negative stereotypes and personal biases about different groups, boost problem-solving capabilities, increase happiness and productivity.
Keywords: Age Diversity; Ethnic Diversity; Market Value Added; National Diversity